2021
DOI: 10.1111/itor.13082
|View full text |Cite
|
Sign up to set email alerts
|

A review on competitive pricing in supply chain management problems: models, classification, and applications

Abstract: Supply chain management (SCM) deals with various strategic, tactical, and operational level decisions in which pricing is of utmost importance to decision makers. Most of the real‐life supply chain pricing problems consider competition as a crucial factor in order to expand the market share and tackle emerging competitors. Accordingly, competitive pricing in SCM has attracted great attention by practitioners and academicians in the last four decades. Now after 40 years, it seems necessary to systematically rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 185 publications
(196 reference statements)
0
3
0
Order By: Relevance
“…It can be suggested that the competitive power distribution in the market affects a firm's position and that firms incorporate this information into their strategic decision making. Thus, franchisors' strategic positioning when they are making pricing decisions is impacted by the competitive condition, which ultimately affects their franchise fee decisions (Sudhir 2001;Ziari et al 2022). Based on this rationale, we argue that competitive conditions moderate the influence of cost-and value-based approaches on franchise fees.…”
Section: Introductionmentioning
confidence: 91%
“…It can be suggested that the competitive power distribution in the market affects a firm's position and that firms incorporate this information into their strategic decision making. Thus, franchisors' strategic positioning when they are making pricing decisions is impacted by the competitive condition, which ultimately affects their franchise fee decisions (Sudhir 2001;Ziari et al 2022). Based on this rationale, we argue that competitive conditions moderate the influence of cost-and value-based approaches on franchise fees.…”
Section: Introductionmentioning
confidence: 91%
“…Besides, the two manufacturers produce substitutable products for the end market. Following the existing literature (Wadecki et al., 2012; Fang and Shou, 2015; Shen et al., 2020; Zhu et al., 2020; Ziari et al., 2022), we suppose that the two manufacturers are engaged in Cournot competition, wherein the market‐clearing prices satisfy pi(Qi,Qj)=ψζiQiγζjQj$p_{i}(Q_{i},Q_{j})=\psi -\zeta _{i}Q_{i}-\gamma \zeta _{j}Q_{j}$. Here, the indexes i,j$i,j$ are in false{1,2false}$\lbrace 1,2\rbrace$ and ij$i\ne j$; ψ>0$\psi >0$ measures the market potential; γfalse[0,1false]$\gamma \in [0,1]$ measures the competition intensity; and Qi$Q_{i}$ represents the order quantity of manufacturer Mi$M_{i}$.…”
Section: Modelmentioning
confidence: 99%
“…, 2018). Recently, due to the difficulties posed by the globalisation of supply, processing and distribution networks, as well as high service demands and competitive pricing, SCM has become increasingly important (Ziari et al. , 2022; Gurtu and Johny, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A timely distribution network is critical for perishable items such as milk since the perishable factor might disrupt the milk supply chain (Wang et al, 2018). Recently, due to the difficulties posed by the globalisation of supply, processing and distribution networks, as well as high service demands and competitive pricing, SCM has become increasingly important (Ziari et al, 2022;Gurtu and Johny, 2021). SCM improves upstream and downstream links for suppliers and customers.…”
Section: Introductionmentioning
confidence: 99%